Preparation of avocado leaf simplicia macro/nano particles by using high energy ball mill. Issue 1 (January 2021) - Ridwan, F; Fadel, M
Abstract: Taguchi method was used to examine high energy ball mill characteristics when producing micro/nano-particles of Simplicia powder using Orthogonal Array (OA) L25. Two factors and five levels were selected for the smallest diameter. The average fineness of the powder produced by high energy ball mill was calculated using the ASTM E11 standard Retsch vibrating sieve machine. The smoothest's fineness value was obtained at a working time of 30 minutes and a shaft rotation speed of 578 rpm with a powder fineness of 181μm. The coarsest fineness value was obtained at 10 minutes of working time and 488 rpm rotating speed with 336μm powder fineness. Obtained the smallest particle diameter has the potential for better absorption of nutrients into the body.